Nilai Kearifan Lokal pada Batik Tradisional Kudus - Ghevira Salsabila; Yully Ambarsih Ekawardhani (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2025)
Batik is an important cultural heritage of Indonesia, particularly in Java. Batik Kudus, crafted by local artisans, reflects the cultural richness of the Kudus region and is influenced by coastal batik styles. Each motif carries symbolic meanings that are closely tied to local traditions and values. This study employs a qualitative descriptive approach to explore the symbolic meanings of Batik Kudus, focusing on how its motifs represent Javanese cultural knowledge through traditional clothing. The purpose of this research is to understand the relationship between batik as an art form and the values of the Kudus community. Batik is not merely seen as fabric or decoration, but as a form of cultural expression that reflects experiences, beliefs, and social values. The findings show that Batik Kudus motifs reflect the identity, lifestyle, and worldview of the local people. These patterns are not only visually appealing but also rich in cultural and spiritual meaning. Thus, Batik Kudus functions as a living tradition—a medium through which the community preserves cultural heritage, tells their stories, and affirms their collective identity.